Isolation of a novel aquaglyceroporin from a marine teleost (Sparus auratus) Function and tissue distribution - Santos, C. R. A. (2014)
The aquaporins (formerly called the major intrinsic protein family) are transmembrane channel proteins. The family includes the CHIP group, which are functionally characterised as water channels and the GLP group, which are specialised for glycerol transport. The present study reports the identification and characterisation of a novel GLP family member in a teleost fish, the sea bream Sparus auratus. A sea bream aquaporin (sbAQP) cDNA of 1047·bp and encoding a protein of 298·amino acids was isolated from a kidney cDNA library. Functional characterization of the sbAQP using a Xenopus oocyte assay revealed that the isolated cDNA stimulated osmotic water permeability in a mercury-sensitive manner and also stimulated urea and glycerol uptake. Northern blotting demonstrated that sbAQP was expressed at high levels in the posterior region of the gut, where two transcripts were identified (1.6·kb and 2·kb), and in kidney, where a single transcript was present (2·kb). In situ hybridisation studies with a sbAQP riboprobe revealed its presence in the lamina propria and smooth muscle layer of the posterior region of the gut and in epithelial cells of some kidney tubules. sbAQP was also present in putative chloride cells of the gill. Phylogenetic analysis of sbAQP, including putative GLP genes from Fugu rubripes, revealed that it did not group with any of the previously isolated vertebrate GLPs and instead formed a separate group, suggesting that it may be a novel GLP member.